(untitled) (International Seven Journal of Health Research, 2023)
Introduction: The aging process undergoes important physiological changes such as decreased muscle strength, loss of balance, cognitive and functional deficit, which directly affect locomotion, making the elderly person a pre-disposition to falls. Objective: This study aims to use physical therapy resources used to prevent falls in the elderly. Materials and Methods: This is a literature review. Studies published between 2016 and 2021 were chosen. The following databases were searched: Latin American and Caribbean Literature in Health Sciences (LILACS) via the Virtual Health Library (VHL); Scientific Electronic Library Online (SciELO); Science direct; Cochrane Brazil; Physiotherapy Evidence Database (PEDro) and Pubmed. Results: 455 titles and abstracts were found using the keywords. Therefore, 443 were excluded for fleeing from the theme and design of the study. Twelve studies were selected to be read in full, of these 5 articles were later excluded. Final considerations: Physical therapy is considered essential to prevent falls in the elderly, which includes diversified exercises focused on improving the musculature both on the ground, as well as making the elderly individual better adapted to the environment in which they live and with greater autonomy, and in the aquatic environment, acting to minimize the reduction in functional capacity.